Improved Non-Invasive Preimplantation Genetic Testing for Beta-Thalassemia Using Spent Embryo Culture Medium Containing Blastocoelic Fluid - Ou, Zhanhui; Deng, Yu; Liang, Yunhao; Chen, Zhiheng; Sun, Ling (Frontiers in Endocrinology, 2022)
Objectives To compare successful beta-thalassemia (β-thalassemia) detection rates obtained using spent culture medium and spent culture medium containing blastocoelic fluid (BF). Method This study involved data from 10 couples who underwent preimplantation genetic testing (PGT) for β-thalassemia. A total of 26 samples of spent culture medium containing BF (group A) and 33 samples without BF (group B) were collected and analyzed. The DNA concentration and β-thalassemia detection rates were evaluated. Results The HBB mutation analysis results of 34 samples were concordant with the biopsy results (34/59, 57.6%). In group A, the HBB mutation analysis results of 19 of 26 samples (73.1%) were concordant with the biopsy results. The concordance rate in group A was higher than that in group B (15/33, 45.5%; P < 0.05). The haplotyping results of 38 samples were concordant with the biopsy results (38/59, 64.4%). The concordance rate in group B was 17/33 (51.5%), which was significantly lower than that in group A (21/26, 80.8%) (P < 0.05). In group A, the mean DNA concentration of samples with <10% fragmentation was 107.3 ± 70.1 ng/μL, which was lower than that of samples with ≥10% fragmentation (194.6 ± 28.0 ng/μL) (P < 0.05). However, the detection rates of <10% and ≥10% fragmentation were not significantly different (P > 0.05). Conclusion The β-thalassemia detection rate with non-invasive PGT using the spent culture medium containing BF was higher than that using the spent culture medium alone. Fragmentation is associated with DNA concentration in the spent culture medium containing BF.